In Vivo Chronic Stimulation Unveils Autoreactive Potential of Wiskott–Aldrich Syndrome Protein-Deficient B Cells - Castiello, Maria Carmina; Pala, Francesca; Sereni, Lucia; Draghici, Elena; Inverso, Donato; Sauer, Aisha V.; Schena, Francesca; Fontana, Elena; Radaelli, Enrico; Uva, Paolo; Cervantes-Luevano, Karla E.; Benvenuti, Federica; et al. (Frontiers in Immunology, 2017)
Wiskott-Aldrich syndrome (WAS) is a primary immunodeficiency caused by mutations in the gene encoding the hematopoietic-specific WAS protein (WASp). WAS is frequently associated to autoimmunity, indicating a critical role of WASp in maintenance of tolerance. The role of B cells in the induction of autoreactive immune responses in WAS has been investigated in several settings but the mechanisms leading to the development of autoimmune manifestations have been difficult to evaluate in the mouse models of the disease that do not spontaneously develop autoimmunity. We performed an extensive characterization of Was-/- mice that provided evidence of the potential alteration in B cell selection, because of the presence of autoantibodies against dsDNA, platelets and tissue antigens. To uncover the mechanisms leading to the activation of the potentially autoreactive B cells in Was-/- mice, we performed in vivo chronic stimulations with TLR agonists (LPS and CpG) and apoptotic cells or infection with Lymphocytic ChorioMeningitis Virus (LCMV). All treatments led to increased production of autoantibodies, increased proteinuria and kidney tissue damage, in Was-/- mice. These findings demonstrate that a lower clearance of pathogens and/or self-antigens and the resulting chronic inflammatory state could cause B cell tolerance breakdown leading to autoimmunity in WAS.